Pediatric Gastrointestinal Endoscopy: Diagnostic Yield and Appropriateness of Referral Based on Clinical Presentation: A Pilot Study - Fachler, Tahel; Shteyer, Eyal; Orlanski Meyer, Esther; Shemasna, Ibrahim; Lev Tzion, Raffi; Rachman, Yelena; Bergwerk, Ari; Turner, Dan; Ledder, Oren (Frontiers in Pediatrics, 2021)
Objectives: There is a lack of evidence-based consensus for the utility of gastrointestinal endoscopy (GIE) in an array of frequently occurring symptoms in children. We aimed to assess the diagnostic yield of endoscopy in an effort to aid clinical decision making. Methods: Retrospective analysis included patients ≤18 years who underwent GIE during one calendar year at Shaare Zedek Medical Center. We excluded children referred for predefined obvious indications for GIE, planned follow-up procedures, and therapeutic endoscopy. Clinician-assigned indication for endoscopy as well as endoscopic and histologic findings were recorded. Diagnostic yield of GIE was determined according to referral indication. Results: There were 794 endoscopies performed of which 329 were included in the analysis (mean age 9.3 ± 5.0 years, 51% female). No significant complications of GIE were recorded. Six major referral indications were identified among which abdominal pain was the most frequent 88/329 (26%) of whom 32/88 (36%) had a significant diagnostic finding. Among the other major indications, diagnostic findings were found in 36/85 (43%) children with primary indication of chronic diarrhea, 14/33 (42%) failure to thrive, 15/32 (46%) short stature, 30/56 (54%) iron deficiency, and 20/48 (42%) weight loss. Conclusions: Pediatric GIE is a safe procedure with diverse clinical indications. The diagnostic yield of endoscopy is variable, depending on the referral indication. These data can assist formulating judicious referral practices.